Correct electrostatic treatment of noncovalent interactions: the importance of polarization. (1st December 2014) - Clark, Timothy; Politzer, Peter; Murray, Jane S.
Abstract : Abstract : The Hellmann–Feynman theorem assures us that the forces felt by the nuclei in a molecule or complex are purely classically electrostatic. Nevertheless, it is often claimed (incorrectly) that electrostatic considerations are not sufficient to explain noncovalent interactions. Such assertions arise largely from neglecting the polarization that is inherently part of the electrostatic interaction, and must be taken into account. Accordingly, we now outline the requirements for a correct electrostatic treatment and discuss the difference between physical observables and quantities that arise from mathematical models. Polarization and donor–acceptor charge transfer are shown to be equivalent for weak interactions. However, polarization is a physical observable while charge transfer, in this context, is mathematical modelling. We also discuss some popular schemes for analyzing noncovalent interactions. WIREs Comput Mol Sci 2015, 5:169–177. doi: 10.1002/wcms.1210 This article is categorized under: Electronic Structure Theory > Ab Initio Electronic Structure Methods Electronic Structure Theory > Density Functional Theory Molecular and Statistical Mechanics > Molecular Interactions